Ingestion of a human-relevant mixture of environmentally sourced microplastics promotes inflammation and tumorigenesis in the mouse colon - Madjid Djouina; Muriel Pichavant; Christophe Waxin; Alexandre Dehaut; Suzie Loison; Emeline Driencourt; Amélie Deborgher; Capucine Balesdent; David Launay; Laurent Dubuquoy; Guillaume Duflos; Mathilde Body-Malapel (Environmental Pollution, 2026)

Ingestion of environmentally sourced polyvinyl chloride microplastic fragments increases colon inflammation and fibrosis in mice - Madjid Djouina; Christophe Waxin; Ségolène Caboche; Alexandre Dehaut; Charlotte Himber; Capucine Balesdent; Dephine Beury; David Hot; Cécile Vignal; David Launay; Laurent Dubuquoy; Guillaume Duflos; et al. (Environmental Research, 2025)

Low dose dietary contamination with deoxynivalenol mycotoxin exacerbates enteritis and colorectal cancer in mice - Madjid Djouina; Christophe Waxin; Ségolène Caboche; Karine Lecointe; Alexander Steimle; Delphine Beury; Mahesh S. Desai; David Hot; Laurent Dubuquoy; David Launay; Cécile Vignal; Mathilde Body-Malapel (Science of The Total Environment, 2023)

Antioxidant and anti-lipase capacities from the extracts obtained from two invasive plants: Ambrosia artemisiifolia and Solidago canadensis - Vanille Quinty; Rouba Nasreddine; Cyril Colas; Alexandra Launay; Reine Nehmé; Ali El-Khiraoui; Christine Piot; Micheline Draye; Emilie Destandau; David Da Silva; Gregory Chatel (Food Bioscience, 2023)

In situ monitoring of galactolipid digestion by infrared spectroscopy in both model micelles and spinach chloroplasts - Moulay Sahaka; Eduardo Mateos-Diaz; Sawsan Amara; Jutarat Wattanakul; David Gray; Dominique Lafont; Brigitte Gontero; Hélène Launay; Frédéric Carrière (Chemistry and Physics of Lipids, 2023)

Conservation resource allocation, small population resiliency, and the fallacy of conservation triage - David A. Wiedenfeld; Allison C. Alberts; Ariadne Angulo; Elizabeth L. Bennett; Onnie Byers; Topiltzin Contreras‐MacBeath; Gláucia Drummond; Gustavo A. B. da Fonseca; Claude Gascon; Ian Harrison; Nicolas Heard; Axel Hochkirch; et al. (Conservation Biology, 2021)
Some conservation prioritization methods are based on the assumption that conservation needs overwhelm current resources and not all species can be conserved; therefore, a conservation triage scheme (i.e., when the system is overwhelmed, species should be divided into three groups based on likelihood of survival, and efforts should be focused on those species in the group with the best survival prospects and reduced or denied to those in the group with no survival prospects and to those in the group not needing special efforts for their conservation) is necessary to guide resource allocation. We argue that this decision‐making strategy is not appropriate because resources are not as limited as often assumed, and it is not evident that there are species that cannot be conserved. Small population size alone, for example, does not doom a species to extinction; plants, reptiles, birds, and mammals offer examples. Although resources dedicated to conserving all threatened species are insufficient at present, the world's economic resources are vast, and greater resources could be dedicated toward species conservation. The political framework for species conservation has improved, with initiatives such as the UN Sustainable Development Goals and other international agreements, funding mechanisms such as The Global Environment Facility, and the rise of many nongovernmental organizations with nimble, rapid‐response small grants programs. For a prioritization system to allow no extinctions, zero extinctions must be an explicit goal of the system. Extinction is not inevitable, and should not be acceptable. A goal of no human‐induced extinctions is imperative given the irreversibility of species loss.

Spatially explicit estimates of N 2 O emissions from croplands suggest climate mitigation opportunities from improved fertilizer management - James S. Gerber; Kimberly M. Carlson; David Makowski; Nathaniel D. Mueller; Iñaki Garcia de Cortazar‐Atauri; Petr Havlík; Mario Herrero; Marie Launay; Christine S. O'Connell; Pete Smith; Paul C. West (Global Change Biology, 2016)
With increasing nitrogen (N) application to croplands required to support growing food demand, mitigating N 2 O emissions from agricultural soils is a global challenge. National greenhouse gas emissions accounting typically estimates N 2 O emissions at the country scale by aggregating all crops, under the assumption that N 2 O emissions are linearly related to N application. However, field studies and meta‐analyses indicate a nonlinear relationship, in which N 2 O emissions are relatively greater at higher N application rates. Here, we apply a super‐linear emissions response model to crop‐specific, spatially explicit synthetic N fertilizer and manure N inputs to provide subnational accounting of global N 2 O emissions from croplands. We estimate 0.66 Tg of N 2 O‐N direct global emissions circa 2000, with 50% of emissions concentrated in 13% of harvested area. Compared to estimates from the IPCC Tier 1 linear model, our updated N 2 O emissions range from 20% to 40% lower throughout sub‐Saharan Africa and Eastern Europe, to >120% greater in some Western European countries. At low N application rates, the weak nonlinear response of N 2 O emissions suggests that relatively large increases in N fertilizer application would generate relatively small increases in N 2 O emissions. As aggregated fertilizer data generate underestimation bias in nonlinear models, high‐resolution N application data are critical to support accurate N 2 O emissions estimates.

Mixed connective tissue disease presenting as trigeminal neuropathy - Bertrand Hamoir; Marianne Giroux; Olivier Outteryck; David Launay; Patrick Vermersch (Acta Neurologica Belgica, 2014)